Protocol for the development of a Core Outcome Set (COS) for hemorrhoidal disease: an international Delphi study - van Tol, R. R. (Int J Colorectal Dis, 2017)
PURPOSE: Over the last decade, many studies were performed regarding treatment options for hemorrhoidal disease. Randomised controlled trials (RCTs) should have well-defined primary and secondary outcomes. However, the reported outcome measures are numerous and diverse. The heterogeneity of outcome definition in clinical trials limits transparency and paves the way for bias. The development of a core outcome set (COS) helps minimizing this problem. A COS is an agreed minimum set of outcomes that should be measured and reported in all clinical trials of a specific disease. The aim of this project is to generate a COS regarding the outcome of treatment after hemorrhoidal disease. METHODS: A Delphi study will be performed by an international steering group healthcare professionals and patients with the intention to create a standard outcome set for future clinical trials for the treatment of hemorrhoidal disease. First, a literature review will be conducted to establish which outcomes are used in clinical trials for hemorrhoidal disease. Secondly, both healthcare professionals and patients will participate in several consecutive rounds of online questionnaires and a face-to-face meeting to refine the content of the COS. DISCUSSION: Development of a COS for hemorrhoidal disease defines a minimum outcome-reporting standard and will improve the quality of research in the future. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00384-017-2833-5) contains supplementary material, which is available to authorized users.